Self-Efficacy Mediates Entrepreneurship Course, Social Environment, Financial Literacy, and E-Commerce Towards Entrepreneurial Interest - Yurisa Dwi Aprilia Ningtias; Elly Astuti; Farida Styaningrum (Jurnal Kewirausahaan dan Bisnis, 2024)
This research aims to determine the influence of entrepreneurship, social environment, financial literacy, and e-commerce courses on students' entrepreneurial interest through self-efficacy as an intervening variable. This type of research is quantitative research with primary data sources. The population of this research is students from the Faculty of Teacher Training and Education in 2020 and 2021 at PGRI Madiun University, with a total of 982 students. The sampling technique uses purposive sampling—data collection techniques through questionnaires. The data analysis technique uses mediating and Structural Equation Modeling (SEM PLS) methods. The research results show that entrepreneurship courses do not have a positive effect on entrepreneurial interest. In contrast, the social environment, financial literacy, e-commerce, and self-efficacy have a positive effect on entrepreneurial interest. Self-efficacy mediates the social environment, financial literacy, and e-commerce on entrepreneurial interest. These findings contribute to the entrepreneurship literature by highlighting the central role of self-efficacy as a mediator, particularly its ability to amplify the effects of external factors such as social environment, financial literacy, and e-commerce.Keywords: e-commerce; entrepreneurship course; entrepreneurial interest; financial literacy; self-efficacy; social environment